Influence of SHGs on Empowerment of Rural Poor - Banshi Lal Sahu; Souvik Ghosh (Journal of Agricultural Extension Management, 2016)
Self Help Group (SHG) has emerged as a potential option/or empowerment of rural poor including women. The present study was conducted in randomly selected Kanker district of Chhattisgarh. A random sample of 12 SHGs, i.e. three from each of the four schemes viz. NABARD 's SHG-Bank Linkage Programme (SBLP}, National Rural Livelihood Mission (NRLM), Integrated Watershed Management Programme (IWMP) and Agricultural Technology Management Agency (ATMA), were selected From each of the 12 SHGs, a sample of 10 members was chosen as respondents. Improvement in overall empowerment of members of the SHGs was observed in general. The highest level of empowerment was in case of members of SHGs under NRLM (mean score of 18.88 out of 25), followed by IWMP (18. 78), SBLP (17.67) and ATMA (16.80). However, the extent of improvement was maximum in case of members of SHGs under ATMA (33%) followed by NRLM (31%), IWMP (28%) and NABARD's SBLP (26%). Among the five indicators of empowerment, overall social empowerment and political empowerment were found to be improved maximum among members of SHGs under SBLP and NRLM, respectively. Empowerment from gender parity point of view was studied in case of women SHGs on the basis of five domains of empowerment. Overall, it was found that members of six SHGs (two each under NRLM, IWMP and SBLP) were empowered from gender parity point of view having a score of 80 per cent and above. The empowerment from gender parity was highest for the women members of SHGs under both NRLM and IWMP followed by SBLP. The members of SHGs under ATMA were not considered empowered from gender parity point of view as the score was less than 80 per cent. Leadership and income domains showed maximum empowerment in case of women members of all SHGs; however, it was varied and relatively less in case of production, resource, and time domains